Factors Influencing the Interaction Between the Public and Government Authorities in Moscow’s Transport Sector: Assessment of Public Opinion - Yu. Yu. Temnikova (Управленческие науки)
The aim of this study was to justify the factors influencing the interaction between government authorities and the public in the field of urban transport within the framework of the “Strategy for the Development of the Transport System of Moscow and the Moscow Region until 2035.” To achieve this, it was necessary to address tasks such as assessing the current level of such interaction and identifying priority tools for its implementation. The article presents an analysis of the dynamics of passenger traffic in Moscow’s urban transport and shows its structure (by mode of transport). A classification of factors is proposed based on the following criteria: financial; accessibility, comfort, and convenience; digitalization; travel speed; transport safety; social and environmental factors; level of infrastructure development; and organizational and regulatory factors. The study employed both general scientific methods — analysis, synthesis, comparison — and applied research methods, including public surveys and statistical processing through correlation analysis. Based on sociological surveys of the megacity’s residents on the topic of transport sector development, the study identified priority tasks and directions for its improvement. The results allow for the justification of development scenarios for the urban agglomeration’s transport system, taking into account public opinion. These data can be used to improve the monitoring system for both urban management and municipal governance.